Metabolite Profile and Metabolic Network Analysis of Walnuts (Juglans regia L.) in Response to Chilling Stress - Kai Liu; Yang Li; Yaxin Sang; Yaru Zhang; Xiuhong An; Hongxia Wang; Ruifen Zhang (Metabolites, 2025)
Background: Walnut (Juglans regia L.) is a species of considerable ecological, social, and economic importance. However, comprehensive metabolomic investigations into walnut cultivars under chilling stress remain scarce. Methods: In this study, we utilized LC-MS/MS-based non-targeted metabolomics to analyze differential metabolites in two walnut cultivars exposed to chilling stress at 0.5 °C for 0 and 48 h. Results: A total of 1504 metabolites were identified, including 871 in positive ion mode and 633 in negative ion mode. Specifically, 160 and 287 differential metabolites were detected in ‘Qingxiang’ and ‘Liaoning No.8’, respectively, under positive ion mode. In negative ion mode, 83 and 206 differential metabolites were identified in ‘Qingxiang’ and ‘Liaoning No.8’, respectively. These metabolites were primarily associated with α-linolenic acid metabolism, phenylpropanoid biosynthesis, flavonoid biosynthesis, and phenylalanine metabolism, and multiple candidate genes were obtained that exhibit significant correlations with metabolites, suggesting their critical roles in the walnut’s response to chilling stress. Conclusions: This study proposes a metabolic network for walnut leaves under chilling stress, enriching our understanding of the metabolic adaptation mechanisms of walnuts to low-temperature conditions. It lays a foundation for investigating the regulatory mechanisms of metabolite synthesis under cold stress and provides important theoretical insights for breeding cold-resistant walnut cultivars.